Desain Rute Terpendek untuk Distribusi Koran - Jan Alif Kreshna; Satria Perdana Arifin; Rika Perdana Sari (UIN Sultan Syarif Kasim Riau, 2011)
Traveling Salesman Problem is a problem how to get the shortest route in a journey. One example for Traveling Salesman Problem is paperboy. Paperboy’s duty is to deliver the papers to each customer so the customer can get information quickly. Therefore, the paperboy must find the shortest route to deliver the papers in a short time. Ant Colony System is a methodology that is generated through observation of the ants. Ant Colony System is a probabilistic technique to solve computational problems by finding the best path through the graph. This algorithm is inspired by the behavior of ants in finding paths from the colony to food. In the Ant Colony System there are a number of artificial ants, which are assigned to find a solution to an optimization problem, one of which find the shortest path. In this research discussed hoe the Ant Colony System can find the shortest route in the delivery of newspapers, so paperboy can deliver newspapers quickly. Keywords: Ant Colony System, Travelling Salesman Problem, Graph.